48 Thrombolysis in STEMI: are the correct patients being identified for routine angiography versus rescue PCI, the west of Ireland experience. (7th October 2015) - Cuddy, S; Yearoo, I; Walsh, R; Mylotte, D; Sharif, F; Bynes, B; MacNeill, B; Crowley, J; Nash, P; Daly, K
Abstract : Thrombolysis is an important reperfusion strategy where primary PCI cannot be offered to STEMI patients within recommended timelines. The National ACS programme recommends the transfer of thrombolysed STEMI patients as soon as possible to a primary PCI centre. In cases of failed thrombolysis the patient should undergo immediate angiography and rescue PCI (RPCI). If thrombolysis is successful a strategy of routine early angiography is recommended. Aim: The aim of this study was to determine the number of thrombolysed patients in the West of Ireland that were appropriately deferred for routine early angiography compared to those that were brought for rescue PCI, as determined by TIMI flow at time of coronary angiography and LV function on echo. Methods: Data on all Code STEMI patients admitted to UHG is collected prospectively. Using this database we identified all patients who were thrombolysed for STEMI in 2014. Results: Of 324 code STEMI admissions to UHG 59 (25.4% female, average age 62, age range 30–95) had received thrombolysis in an outside hospital. 27 (45.7%) were brought immediately to the lab on arrival at UHG; 14 (51.8%) had TIMI 1 or 0 flow, 13 (48.2%) had TIMI 2–3 flow. The main indication for immediate angiography was ongoing pain and STEMI. 30 (53.3%) patients had routine angiography; 4 (13.3%) had TIMI 0 or 1 flow, 26 (86.7%) had TIMI 2 or 3 flow. 2 (3.3%) patients had no angiography, 1 (1.7%) patient was too unstable and did not survive to discharge. The total mortality in the thrombolysed group was 4. Of the group brought for RPCI 24 (89%) proceeded to PCI, no intervention required in 3 (11%) cases, 2 of these being a 'false call' (LBBB, pericarditis), 2 patients in this subgroup did not survive. 62% had impaired LV function on initial echo, 38% with severely impaired LV function (EF <35%). In the routine angiography subgroup 23 (75.5%) proceeded to PCI, 1 patient did not survive following PCI, 2 (6.6%) were referred for CABG, 4 (13.3%) did not require intervention, 1 patient was judged to have a CTO. 52% had impaired LV systolic function, 8% severely impaired. Comparing TIMI flow in the 2 subgroups there is a statistical significance (p < 0.001). When comparing the groups looking at LV function by classing it as normal to mildly impaired versus moderate to severe LV dysfunction the difference was significant between the 2 subgroups, the group brought straight to the lab having worse function (p = 0.01). Conclusion: In our cohort of thrombolyed patients from the West of Ireland we found that the appropriate patients are being identified as successfully thrombolysed and having routine early angiography in keeping with international guidelines. This is demonstrated by the statistically significant difference in TIMI flow and initial LV systolic function between the 2 groups, highlighting that the delayed group are correctly identified as having a smaller ischaemic burden.